The antimicrobial peptide Polybia-MP1 differentiates membranes with the hopanoid, diplopterol from those with cholesterol - Alvares, Dayane S. [UNESP]; Monti, Mariela R.; Ruggiero Neto, João [UNESP]; Wilke, Natalia (Elsevier, 2021)
Polybia-MP1 is an antimicrobial peptide that shows a decreased activity in membranes with cholesterol (CHO). Since it is now accepted that hopanoids act as sterol-surrogates in some sterol-lacking bacteria, we here inquire about the impact of Polybia-MP1 on membranes containing the hopanoid diplopterol (DP) in comparison to membranes with CHO. We found that, despite the properties induced on lipid membranes by DP are similar to those induced by CHO, the effect of Polybia-MP1 on membranes with CHO or DP was significantly different. DP did not prevent dye release from LUVs, nor the insertion of Polybia-MP1 into monolayers, and peptide-membrane affinity was higher for those with DP than with CHO. Zeta potentials (ζ) for DP-containing LUVs showed a complex behavior at increasing peptide concentration. The effect of the peptide on membrane elasticity, investigated by nanotube retraction experiments, showed that peptide addition softened all membrane compositions, but membranes with DP got stiffer at long times. Considering this, and the ζ results, we propose that peptides accumulate at the interface adopting different arrangements, leading to a non-monotonic behavior. Possible correlations with cell membranes were inquired testing the antimicrobial activity of Polybia-MP1 against hopanoid-lacking bacteria pre-incubated with DP or CHO. The fraction of surviving cells was lower in cultures incubated with DP compared to those incubated with CHO. We propose that the higher activity of Polybia-MP1 against some bacteria compared to mammalian cells is not only related to membrane electrostatics, but also the composition of neutral lipids, particularly the hopanoids, could be important.
Keywords: Bacterial resistance; Lytic activity; Membrane dynamic elasticity; Optical tweezers; Targeting of AMPs; Zeta potential